2015
DOI: 10.1080/01694243.2015.1061905
|View full text |Cite
|
Sign up to set email alerts
|

Electrically conductive adhesives based on acrylate resin filled with silver-plated graphite nanosheets and carbon nanotubes

Abstract: Using the electroless plating method, the silver particles were successfully coated on the surface of graphite nanosheets (GNs) and carbon nanotubes (CNTs). Energydispersive spectrometer images showed that the content of silver was about 30-55 wt%, which were supported by the X-ray diffraction images and scanning electronmicroscopy images. Taking advantage of the 'Synergistic Effects' occurring between fillers with different morphologies, we were able to obtain silver-plated graphite nanosheets (Ag/GNs) and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…After identifying the electrical and adhesion properties of the PMS:PEDOT ( 5 ), we compared the test result to the previously reported ECAs’ values. ,, , The ECAs used for comparison were metal (Ag, Zn, or Fe)-containing ECAs, carbon material-based ECAs, and ICP-based ECAs. The Ag-, Zn-, Fe-containing, carbon material-based and ICP-based ECAs are represented as gray, magenta, blue, black, and green dots, respectively, with corresponding reference in the graph (Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After identifying the electrical and adhesion properties of the PMS:PEDOT ( 5 ), we compared the test result to the previously reported ECAs’ values. ,, , The ECAs used for comparison were metal (Ag, Zn, or Fe)-containing ECAs, carbon material-based ECAs, and ICP-based ECAs. The Ag-, Zn-, Fe-containing, carbon material-based and ICP-based ECAs are represented as gray, magenta, blue, black, and green dots, respectively, with corresponding reference in the graph (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Although ICPs provide unique advantages such as lightness, the ICP filler containing ECA is rare in the literature. There are a handful of examples reporting ICP filler containing ECAs that demonstrate a much lower overall performance compared with metal (Ag)-containing ECAs. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Ma et al blended acrylate resin with Ag-CNTs and Ag-GNs to synthesize a new conductive adhesive (ECA) and found that the conductivity reached 8.71 S/cm and the shear strength was 0.47 MPa when the concentration of the composite filler was 30 wt% (21 wt% of Ag-GNs and 9 wt% of Ag-CNTs) ( Huan et al, 2015 ). Zhao et al prepared CNTs-Ag composites by solution ball milling (SBM) of silver-plated CNTs (Ag-CNTs) obtained by plain chemical plating (CEP) and ultrasonic spray atomization (EPUSA), respectively, with Ag powder, followed by densification by spark plasma sintering (SPS).…”
Section: Application Of Carbon Nanotubes After Electroless Platingmentioning
confidence: 99%
“…Carbon materials are usually introduced to organic polymer PCMs to regulate the electric heating performance because of their advantages of low density and electrical/thermal conductivity 12 . Ma 13 and Chen 14 studied the influence of adding a silver conductive matrix on polymer, and conducted a preliminary exploration of the optimization methods and mechanisms of the electro‐thermal performance of the polymer. The polyurethane (PU)/graphite foam composite was prepared, and high electric/photo‐thermal conversion efficiency was achieved 15 .…”
Section: Introductionmentioning
confidence: 99%